Rational, Reasonable and Nudged Man - Zorzetto, Silvia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This paper is part of a broader enquiry into three main models (or concepts) of individual, which appear in philosophical and legal discourse: the Reasonable Person, the Biased Nudged Human, the Homo OEconomicus (or the Economic Rational Man), The overall research aims to clarify the differences and similarities between such models as used by the relevant classical literature. The general purpose of the research is mainly to understand whether these models overlap or resemble each other and, if so, to what extent. The paper focuses on the theses that: (i) the different literatures concerned with these models of individual should be confronted more critically and, in particular, a closer dialogue between studies concerning reasonableness and nudging should be fruitful; (ii) a significant distance exists between the legal uses of these models and their use in theoretical and philosophical speculation. This is particularly true with regard to the Reasonable Person and the Homo OEconomicus concepts. Although legal scholars refer to them, such references are often nothing more than embellishments. In many instances, they import concepts and conceptions from other fields of investigation or literature by making a spurious and superficial analogy. Keywords: Rationality; Reasonableness; Nudging, Individuals; Law Index: 1. Introduction – 2. The Reasonable Person and the Man on the Clapham Omnibus – 3. Econs and Humans: Biases and Nudges – 4. Homo OEconomicus: a Cluster of Models – References